Leader’s moral intelligence and employees’ affective commitment: the mediating role of transformational leadership - Mamede, Cláudia (2014)
The study shows how leader‟s moral intelligence predicts employees‟ affective commitment and if transformational leadership mediates such relationship. One hundred and sixty nine employees from 117 organizations operating in Portugal from the secondary and services sectors participated. Leaders reported their moral intelligence, their subordinates having described their own affective commitment and their perceptions of transformational leadership. The results suggest that moral intelligence predicts employees‟ affective commitment, and that transformational leadership fully mediates such relationship. Considering that employees‟ affective commitment influences their performance, our study suggests that leaders‟ moral intelligence may indirectly promote employees‟ and organizational performance.